Some political and legal views in the teachings of al-Farabi (Journal of actual problems of jurisprudence, 2023)
The article is devoted to the study of important state-legal issues in political, cultural and spiritual history, where the name of the philosopher al-Farabi as a person and his priceless heritage rightfully occupies one of the key places. Al-Farabi's socio-political ideas can certainly be seen as an attempt to design an ideal human union based on universal harmony. His main goal, in our opinion, would be to achieve happiness in society, and this is how to try to theoretically solve the socio-moral problems of his time. We believe that the appeal to the work of the famous philosopher is relevant for any sovereign state in the world, especially due to the recent events taking place in the world.Thus, al-Farabi's society is primary in relation to the state, while the state, like any society, is the only possible way for a person to fully exist, based on moral and religious values.Wise al-Farabi defines his political and legal reflections within the framework of a holistic philosophical understanding of the world, for example, to create a harmonious society, according to him it is possible only through the knowledge of the harmony of the cosmos and its component parts (the First, Second causes and Active reason), and this allows you to open the way to eternal knowledge.Keywords: virtue, achievement of happiness, ethics, society, ignorant city, collective city